Evaluation of the recirculation process of aerobic sludge from a percolating biological filter in an upflow anaerobic sludge blanket digestion reactor, with characterization of sludge solids - Gomiero, Fernando Z.; Knopik, Marco A.; Velho, Julia Carnelós M. [UNESP]; Gonçalves, José Eduardo; Velho, Luiz Felipe M. (Elsevier, 2021)
In this work, the sustainability indicators from a sewage treatment plant in a Southern Brazilian city, with a combined system of anaerobic treatment by upflow anaerobic sludge blanket (UASB) reactor and aerobic treatment with a percolating biological filter (PBF), were assessed. The need for the process of recirculation and anaerobic digestion of excess sludge in upflow anaerobic sludge blanket digestion (UASB) reactors and the influence of this procedure on the efficiency of each treatment step were evaluated. The production and volume of sludge produced in the treatment units were also calculated for periods with and without the recirculation of the sludge. The sludge characterization results showed values of 4.7% for total solids (TS) and 65% for total volatile solids (TVS) for the UASB reactor sludge, and 2.9% TS and 69% TVS for the PBF sludge. The efficiency of the effluent treatment by the combined system UASB + PBF + desiccator remained stable for both periods analyzed and was 85% for chemical oxygen demand, 88% for biological oxygen demand and 89% for total suspended solids. Finally, it was shown that these results are similar to those obtained for the activated sludge system, but the combined system has the advantage of being more sustainable.
Keywords: Hydraulic load; Percolating biological filter; Percolator filter; Sewage treatment; Sludge characterization and stability; Treatment plant efficiency; Upflow anaerobic sludge blanket